2014
DOI: 10.3389/fpsyg.2014.01278
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face or face-to-screen? Undergraduates' opinions and test performance in classroom vs. online learning

Abstract: As electronic communication becomes increasingly common, and as students juggle study, work, and family life, many universities are offering their students more flexible learning opportunities. Classes once delivered face-to-face are often replaced by online activities and discussions. However, there is little research comparing students' experience and learning in these two modalities. The aim of this study was to compare undergraduates' preference for, and academic performance on, class material and assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
244
2
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(272 citation statements)
references
References 33 publications
17
244
2
9
Order By: Relevance
“…Compared with recording and broadcasting, live teaching is more interactive, can create a learning atmosphere, and can solve the problem of mandatory learning to a certain extent [3] . The combination of live broadcast technology and online education has a stronger appeal and freshness for the Internet generation, and can more exibly compensate for the lack of online learning interaction [4] . This brings opportunities for the online education industry, and live broadcast education has gradually begun to rise.…”
Section: Analysis Of Chinese Dental Professional Coursesmentioning
confidence: 99%
“…Compared with recording and broadcasting, live teaching is more interactive, can create a learning atmosphere, and can solve the problem of mandatory learning to a certain extent [3] . The combination of live broadcast technology and online education has a stronger appeal and freshness for the Internet generation, and can more exibly compensate for the lack of online learning interaction [4] . This brings opportunities for the online education industry, and live broadcast education has gradually begun to rise.…”
Section: Analysis Of Chinese Dental Professional Coursesmentioning
confidence: 99%
“…Even this development is very influential in the world of Education. Learning can be done without face to face directly between the teacher and students [2]. Teachers can provide teaching materials in digital content that can be accessed, stored, shared anytime and anywhere via the internet [3].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the Psychology Department of the University of Tasmania, Australia revealed that there was no significant difference in the academic performance of students in face to face class and online classes (Kemp and Grieve, 2014). Virtual laboratory for conducting practical classes have already been introduced in different faculties of science like Physics (Finkelstein et al, 2005), Biology (Muhamad et al, 2010), Engineering (Rajendran et al, 2010), Chemistry (Bakar et al, 2013) and have been found to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…This technology is not applied in medical students of Bangladesh. The virtual class can be the best method of conducting classes to overcome the physical boundaries of the classroom and students would be able to do the class at a time of their own choice, without having to travel to anywhere (Kemp and Grieve, 2014). Some universities and colleges around the world offer online degree programs and courses, which give students the opportunity to access higher education from anywhere (The complete…”
Section: Considering Three Teachers At the Level Of Assistantmentioning
confidence: 99%